Dampak Perkembangan Anak yang Ditinggal oleh Orang Tua Bekerja - Febriana, Nabila; Ridwan, Ahmad (As-Syar i: Jurnal Bimbingan & Konseling Keluarga, 2025)
This study discusses the psychological and social impacts experienced by children who grow up in families where both parents work. The main goal is to understand how this situation affects children's emotional development, social relationships, and overall well-being. The method used is a qualitative approach through literature review, collecting data from various articles, journals, and previous research reports. The findings show that children raised by parents who are both busy working often feel lonely, emotionally distant from their parents, and struggle to develop social skills. However, some children also grow to become more independent, responsible, and adaptable to their environment. Factors such as the parenting style applied, the presence of other family members as caregivers, and the quality of time and communication between parents and children greatly influence the extent to which negative impacts can be minimized. Therefore, it is important for parents to find a balance between work and family life, and to implement parenting strategies that are attentive and supportive to ensure the child’s development remains optimal, even in challenging circumstances.